Phenomenology of Communication of Generation Z in Pekanbaru - Anwar, Tika Mutia (Komunikator, 2019)
The Generation Z and its capability in following the latest technological developments create a new phenomenon, ranging from their lifestyle that so close with information and technology to the communication style; not to mention their domination in social media communication. Uniquely, they tend to believe that their lives in social media are more essential than in the real world. This study uses an interpretive paradigm with a qualitative approach. The research subject isGeneration Z in Pekanbaru while the object is the phenomenology of communication of Generation Z. The study finds two categorizations of Generation Z’s selfrepresentation in Pekanbaru, namely: "The Influencer" and "The Followers." Furthermore, verbally, they often use informal language and slang and have difficulties in face-to-face communication. Nonverbally, they possess informal intonation, follow the latest fashion trends, and are expressive in social media.